Exploring career success among women engineers: The Malaysian case - Johari, Husna; Mat, Norsiah; Mat, Norazuwa; Othman, Siti Norezam; Mohamed, Aini Hayati (Contemporary Research Center (CRC), Australia, 2013)
Since the beginning of the 1960’s, women have increasingly entered into the career occupations and professions.However, those women that began their careers towards the mid-70’s and the early 80’s were considered as those set of women that tried to have it all in relation to their professional career success and family work balance (Gordon & Whelan, 1998; Auster & Ekstein, 2005).It should be noted that women workforce in Malaysia had increased tremendously.In terms of population, women account for about the half of the total number of Malaysian population (Ismail & Ibrahim, 2008).Hence they were found participating in many sectors of the economy such as agriculture, manufacturing, business and service organizations, in addition to their traditional or domestic un-paid sector of the economy.Thus over the years, the percentage of women in the workforce had continued to increase since the period of the year 2000 upward and is expected to continue.